Longitudinal validity of abdominal adiposity assessment by regional bioelectrical impedance - Alvero-Cruz, José Ramón; García-Romero, Jerónimo; Carrillo-de-Albornoz, Margarita; Jimenez Lopez, Manuel; Correas-Gómez, Lorena; Peñaloza, Piero; López-Fernández, Iván; Álvarez-Carnero, Elvis (Springer Nature, 2018)
The main goal of this study was to analyze the longitudinal agreement between changes in trunk and abdominal adiposity variables assessed by DXA and portable bioimpedance device (ViScan). A total of 44 women, enrolled in a 4-month exercise intervention, were included in this analysis. Trunk/abdominal compartments were assessed by ViScan and DXA. Adjusted correlations for age and FM at first assessment (pre) were utilized to perform concurrent validation among methods and completed with an agreement analysis. We observed significant differences between the changes detected by DXA and ViScan for %TFM (difference = -1.41%; p < 0.05), and proportional bias (Kendall's Tau = 0.53; p < 0.0001). Changes in abdominal adiposity were similar (difference = -0.1037 z-score units, p = 0.53), although there was proportional bias (Kendall's Tau = -0.24, p < 0.022). ViScan has a limited capability to evaluated changes in trunk and abdominal adiposity, at least for clinical purposes in adult women. © 2018 Macmillan Publishers Limited, part of Springer Nature.
Keywords: Obesidad; Abdomen - Medición; Abdomen; Absorptiometry; Photon; Adiposity; Adult; Anthropometry; Body Composition; Electric Impedance; Female; Humans; Intra-Abdominal Fat; Longitudinal Studies; Middle Aged; Obesity; Abdominal; Reproducibility of Results; Torso